2021
DOI: 10.1002/ana.26127
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in HID1 Cause Syndromic Infantile Encephalopathy and Hypopituitarism

Abstract: Objective: Precursors of peptide hormones undergo posttranslational modifications within the trans-Golgi network (TGN). Dysfunction of proteins involved at different steps of this process cause several complex syndromes affecting the central nervous system (CNS). We aimed to clarify the genetic cause in a group of patients characterized by hypopituitarism in combination with brain atrophy, thin corpus callosum, severe developmental delay, visual impairment, and epilepsy. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These data suggest that a defect in LDCV formation is the underlying cause of the symptoms associated with this patient. Recent work also reported that mutations in HID-1 patients cause an early infantile encephalopathy with hypopituitarism [ 37 ] and further underscores that HID-1 plays a key role in the regulated secretory pathway. Unraveling its mechanisms of action might help us better understand diseases of the endocrine system and of the brain.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These data suggest that a defect in LDCV formation is the underlying cause of the symptoms associated with this patient. Recent work also reported that mutations in HID-1 patients cause an early infantile encephalopathy with hypopituitarism [ 37 ] and further underscores that HID-1 plays a key role in the regulated secretory pathway. Unraveling its mechanisms of action might help us better understand diseases of the endocrine system and of the brain.…”
Section: Resultsmentioning
confidence: 98%
“…A homozygous mutation within HID-1 has been found in human patients with severe endocrine and neurological deficits [ 31 , 37 ]. This base-pair duplication leads to a frameshift at the end of HID-1 C-terminus ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation